Pengaruh Penambahan Wortel Terhadap Kandungan Vitamin A dan Daya Terima Nugget Ikan Gabus (Channa striata) - Dina Eka Wulandari; Arya Ulilalbab (Yayasan Literasi Sains Indonesia, 2023)
One of the public health problems is vitamin A and protein-energy deficiency. To overcome this problem, innovation is needed to make products made from local ingredients as a source of protein intake and beta-carotene as an ingredient in vitamin A formation. This study aims to analyze the effect of adding carrots on vitamin A content according to DKBM and the acceptability of cork fish nuggets. This study used is a Completely Randomized Design (CRD) with 2 treatments and 1 control involving 90 panelists in an organoleptic test. The results of the study on the content of energy, protein, and vitamin A according to DKBM show that the content of vitamin A in nuggets with the addition of carrots is higher than in nuggets without the addition of carrots. Friedman sig. test α = 0.05, showing that no effect in terms of color (α = 0.855) and texture (α = 0.057). There is an effect in terms of aroma (α = 0.005) and taste (α = 0.008). The result of the acceptability test on cork fish nugget from 82% color parameters and 90% texture is on the P1 product (without the addition of carrots), for the most preferred aroma parameter is P2 (10% carrots) with a percentage of 91.1% and for the parameter of taste, the most preferred taste is P3 (20% carrot) with a percentage of 92.2%. It is necessary to develop nugget products with the formulation of ingredients that can improve nugget texture.